The metal-semiconductor transition monitored by excited state lifetimes of Al4Om− clusters - Koyasu, Kiichirou; Braun, Christian; Proch, Sebastian; Ganteför, Gerd (My University, 2010)
The lifetimes of electronically excited states of Al4O m − clusters are measured for m=1,3,4,5, and 6 using time-resolved photoelectron spectroscopy. With increasing number of oxygen atoms the lifetimes increase. This can be explained qualitatively by a metal-semiconductor transition occurring between the metal-like Al4 − cluster and the fully oxidized semiconductor-like Al4O6 − cluster. Long lifetimes of electron-hole excitations are characteristic for semiconductors, while in metals the strong interaction between the delocalized electrons causes short lifetimes.
Keywords: 530